19.0k views
3 votes
Simplify the expression (1 - 3n3 + 2n4) + (8n4 – 13 – 7)

User GuillaumeA
by
5.8k points

1 Answer

1 vote

Answer:

=
10n^4 - 3n^3 -20

Explanation:

Given that:

=(1 - 3n3 + 2n4) + (8n4 – 13 – 7)

By opening the brackets we get:

= 1-3n3 +2n4 +8n4 -13 -7

By adding like terms: Constants into constants and variables with same powers of x.....

= -20 - 3n3 +10n4

So by arranging the answer in decreasing order of powers of x:

=
10n^4 - 3n^3 -20

I hope it will help you!

User Mingliang Liu
by
5.1k points